Cost-effective complete genome sequencing using the MinION platform for identification of recombinant enteroviruses - Chien, Yeh Seng; Chen, Feng Jui; Wu, Han Chieh; Lin, Chieh Hua; Chang, Wen Chiung; David, Perera; Yang, Jyh Yuan; Lee, Min Shi; Liao, Yu Chieh (American Society for Microbiology, 2023)
Enteroviruses (EVs) are a group of viruses that cause various human illnesses. While the CODEHOP (COnsensus-DEgenerate Hybrid Oligonucleotide Primer) method can generate VP1 gene fragments for enterovirus genotyping, it is unable to detect recombinant strains. Recent advances in viral genome sequencing using next-generation sequencing technologies have enabled comprehensive analyses. However, the high cost poses a challenge for widespread adoption. To address this issue, this study proposes a cost-effective approach for generating complete enterovirus genome sequences using the Oxford Nanopore MinION sequencer. This protocol not only facilitates the generation of accurate genome sequences for various enterovirus strains but also allows for the differentiation of co-infections from viral isolates. In addition, the method can generate polyprotein sequences as well as peptide sequences of the upstream ORF (uORF) whose expression can impact virus infection. Through the analysis of complete enterovirus genomes, this study successfully identified seven enterovirus A71 isolates obtained during the 2018 enterovirus outbreak in Malaysia and Taiwan as recombinants between enterovirus A71 and coxsackievirus A2. Furthermore, our study has made a significant discovery by establishing a strong correlation between uORF trees and the epidemics of EVA71. This finding highlights the potential of uORF sequences as valuable indicators for monitoring and understanding the spread of EVA71 infections. We also identified notable amino acid changes in the transmembrane domain of the uORF protein within a newly identified lineage. These findings provide crucial insights into the molecular characteristics and evolutionary dynamics of EVA71, offering valuable information for future research and intervention strategies.